2020
DOI: 10.3389/fnins.2019.01429
|View full text |Cite
|
Sign up to set email alerts
|

LAO-NCS: Laser Assisted Spin Torque Nano Oscillator-Based Neuromorphic Computing System

Abstract: Dealing with big data, especially the videos and images, is the biggest challenge of existing Von-Neumann machines while the human brain, benefiting from its massive parallel structure, is capable of processing the images and videos in a fraction of second. The most promising solution, which has been recently researched widely, is brain-inspired computers, so-called neuromorphic computing systems (NCS). The NCS overcomes the limitation of the word-at-a-time thinking of conventional computers benefiting from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Such time-dependent shifts of precession frequency controlled by laser-induced anisotropy changes may be further exploited in optically reconfigurable magnonic devices based on tuning the magnetostatic wave dispersion [40]. The possibility to tune the eigenfrequency of magnetic dynamics may find its application in the realization of laser-assisted spintorque nano-oscillators [48].…”
Section: Discussionmentioning
confidence: 99%
“…Such time-dependent shifts of precession frequency controlled by laser-induced anisotropy changes may be further exploited in optically reconfigurable magnonic devices based on tuning the magnetostatic wave dispersion [40]. The possibility to tune the eigenfrequency of magnetic dynamics may find its application in the realization of laser-assisted spintorque nano-oscillators [48].…”
Section: Discussionmentioning
confidence: 99%
“…Electrically controlled spin-orbitronic devices with a clear critical magnetization switching current are therefore capable of mimicking such artificial neurons in principle ( Diep et al., 2014 ; Sengupta et al., 2015b ; Kurenkov et al., 2019 ), but the magnetization states of such nonvolatile neurons may have to be initialized after each fire. The volatile spin-torque nano-oscillator (STNO) ( Torrejon et al., 2017 ; Farkhani et al., 2019 ; Liang et al., 2020 ), a specific type of STT-MTJ that oscillates spontaneously with a low d.c. current-tunable precession amplitude and finite magnetization relaxation, has recently been experimentally demonstrated as an efficient artificial neuron for speech recognition owing to its stability, low noise, and high nonlinearity of frequency and amplitude. As the spin-orbitronic version of STNO, spin hall nano-oscillators (SHNOs) had been also developed to implement as neurons ( Sato et al., 2019 ; Zahedinejad et al., 2020 ); however, as depicted in Figure 1 E, the relationship between the magnetic damping and the SOT-induced in-plane damping-like torque in a PMA-FM is not as symmetrical as the case of STT shown in Figure 1 B; hence, challenges and new opportunities coexist in proposing such an artificial neuron based on the PMA SHNO ( Fulara et al., 2019 ) in the absence of an in-plane magnetic field.…”
Section: Emerging Spin-orbitronic Devices Applicationsmentioning
confidence: 99%
“…It is reported that there is no need to switch back and forth the free layer magnetization and thus the recovery step during information processing is faster (%600 ps) compared to a few nanoseconds in the case of switching. [49] Other than MTJ devices, a spin Hall nano-oscillator based on NiFe nanostructures was proposed. [50] The mutual synchronization of a large number of nano-oscillators showed a large signal quality factor compared to MTJ-based devices.…”
Section: Spintronic Nano-oscillator For Ncmentioning
confidence: 99%